Evaluating the Effects of Benzoic Acid on Finishing Pig Growth Performance - Katelyn N. Gaffield; Mike D. Tokach; Robert D. Goodband; Jason C. Woodworth; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 2,106 pigs (PIC 337 × 1050; initially 73.5 ± 4.21 lb) were used in a 101-d growth study to evaluate the effects of dietary benzoic acid level on grow-finish pig growth performance and carcass characteristics. Pens of pigs (27 pigs per pen) were randomly assigned to 1 of 3 dietary treatments with 13 pens per treatment. Dietary treatments were corn-soybean meal-DDGS-based with an inclusion of none, 0.25, or 0.50% benzoic acid (VevoVitall, DSM Nutritional Products, Parsippany, NJ). Diets were fed in 4 phases from 74 to 110, 110 to 165, 165 to 220, and 220 to 290 lb body weight. In the grower period (d 0 to 44), there was no evidence of differences (P>0.10) for pigs fed increasing benzoic acid for any growth response criteria. For the finisher period (d 44 to 101) and overall (d 0 to 101), increasing benzoic acid tended to increase ADFI (linear,P<0.10) and worsen F/G (linear,P<0.01). There was no evidence of differences in ADG (P>0.10) for the overall experimental period. For carcass characteristics, no evidence of differences (P>0.10) were observed. In conclusion, these data suggest that feeding benzoic acid in the grow-finish period had no impact on ADG, but tended to increase ADFI and worsen F/G.
Keywords: acidifier; benzoic acid; grow-finish pig; growth performance